Identification of absolute geometries of cis and trans molecular isomers by Coulomb Explosion Imaging - Ablikim, U.; Bomme, C.; Xiong, H.; Savelyev, E.; Obaid, R.; Kaderiya, B.; Augustin, S.; Schnorr, K.; Dumitriu, I.; Osipov, T.; Bilodeau, R.; Kilcoyne, D.; et al. (My University, 2016)
An experimental route to identify and separate geometric isomers by means of coincident Coulomb explosion imaging is presented, allowing isomer-resolved photoionization studies on isomerically mixed samples. We demonstrate the technique on cis/trans 1,2-dibromoethene (C2H2Br2). The momentum correlation between the bromine ions in a three-body fragmentation process induced by bromine 3d inner-shell photoionization is used to identify the cis and trans structures of the isomers. The experimentally determined momentum correlations and the isomer-resolved fragment-ion kinetic energies are matched closely by a classical Coulomb explosion model.
Citation: Ablikim, U., Bomme, C., Xiong, H., Savelyev, E., Obaid, R., Kaderiya, B., . . . Rolles, D. (2016). Identification of absolute geometries of cis and trans molecular isomers by Coulomb Explosion Imaging. Scientific Reports, 6, 8. doi:10.1038/srep38202
Keywords: Photoactive Yellow Protein; 3-Body Dissociations; Gas-Phase; Dynamics; Isomerization; Configuration